Fibula osteofascial flap with proximal skin paddle for intraoral reconstruction. Issue 4 (29th July 2016) - Maldonado, Andrés A.; Langerman, Alexander
Abstract : Background: the fibula free flap has become a workhorse in intraoral reconstruction. However, its skin paddle has multiple drawbacks. The aim of this report is to establish the applicability of the fibula osteofascial flap in intraoral reconstruction. Methods: prospectively maintained database was performed in 15 patients who underwent fibula osteofascial flap for intraoral reconstruction. Mandibular reconstruction was the main location (13 patients). Ten flaps were done following tumor resection, three due to osteoradionecrosis and two following mandible fracture/bone loss. A standard fibula flap dissection performing an anterior approach was done, adding a distal fascial flap isolated on the distal perforators (for intraoral reconstruction) and a proximal skin paddle (for external soft tissue reconstruction). Results: One flap was lost due to hypercoagulable state. Fourteen flaps survived with complete oral mucosalization, resembling physiological intraoral bone coverage by 7 weeks (range: 6–8 weeks). One patient presented with delayed donor‐site wound healing. The mean follow‐up was 14.4 months (range: 2–33 months). Thirteen patients (87%) were without tracheotomy at last follow‐up, and 14 patients (93%) were taking at least some nutrition by mouth. Conclusion: Fibula osteofascial flap can be safely used for intraoral reconstruction. This flap provides a stable, thin, and vascularized fascia over the fibula with minimal donor‐site complications. © 2016 Wiley Periodicals, Inc. Microsurgery, 2016. © 2016 Wiley Periodicals, Inc. Microsurgery 37:276–281, 2017.